2006
DOI: 10.1002/cbic.200500264
|View full text |Cite
|
Sign up to set email alerts
|

The RNA‐Cleaving Bipartite DNAzyme Is a Distinctive Metalloenzyme

Abstract: Much interest has focused on the mechanisms of the five naturally occurring self-cleaving ribozymes, which, in spite of catalyzing the same reaction, adopt divergent strategies. These ribozymes, with the exception of the recently described glmS ribozyme, do not absolutely require divalent metal ions for their catalytic chemistries in vitro. A mechanistic investigation of an in vitro-selected, RNA-cleaving DNA enzyme, the bipartite, which catalyzes the same chemistry as the five natural self-cleaving ribozymes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…After 1 min, as with the water solution, no Melgar and Goldthwait (1968) showed that monovalent Na + ions have an inhibitory effect on DNase I activity, whereas additional Mg 2+ ions could increase the activity. However, Mg 2+ ions are an important co-factor for DNAzymes and therefore are preferred additives for formulations (Feldman et al, 2006). Furthermore, Mg 2+ ions decrease DNase II activity, which primarily takes place in the epidermis (Murai et al, 1980) and are known for their stabilising effect on eczematous skin (Denda et al, 1999).…”
Section: Investigation Of the Protective Character Of Different Delivmentioning
confidence: 99%
“…After 1 min, as with the water solution, no Melgar and Goldthwait (1968) showed that monovalent Na + ions have an inhibitory effect on DNase I activity, whereas additional Mg 2+ ions could increase the activity. However, Mg 2+ ions are an important co-factor for DNAzymes and therefore are preferred additives for formulations (Feldman et al, 2006). Furthermore, Mg 2+ ions decrease DNase II activity, which primarily takes place in the epidermis (Murai et al, 1980) and are known for their stabilising effect on eczematous skin (Denda et al, 1999).…”
Section: Investigation Of the Protective Character Of Different Delivmentioning
confidence: 99%
“…The reported variants can be used to cleave 14 out of the 16 possible dinucleotide junctions. (D) The bipartite deoxyribozyme, named as such because of the clustering of purine versus pyrimidine nucleotides in the enzyme region [23,24]. (E) The Na8 deoxyribozyme, which does not require any divalent metal ion for its activity [25].…”
Section: Dna-catalyzed Rna Ligationmentioning
confidence: 99%
“…RNA-cleaving deoxyribozymes other than the 10-23 and 8-17 have also been identified (e.g., Fig. 3D) [23,24], including some DNA enzymes that do not require any divalent metal ion cofactor (e.g., Fig. 3E) [25,26] and another that requires the amino acid histidine as an obligatory cofactor [27] ( Fig.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, the bipartite DNAzyme favors purine-purine (Pur-Pur) and purine-pyrimidine (Pur-Pyr) junctions, 18 while the 10-23 DNAzyme favors Pur-Pyr linkages. 28,29 Recently, through a systematic mutational analysis, we designed several variants of the [8][9][10][11][12][13][14][15][16][17] DNAzyme to cleave all possible dinucleotide junctions of RNA with catalytic rates from 0.00001 to 10 min − 1 . 15 Since efficient cleavage for Pyr-Pyr junctions was not observed in this study, we then sought to isolate more efficient motifs from a focused in vitro selection experiment using a 20-nt random DNA library to ensure that all 8-17 sequence variations were represented in the initial sequence pool.…”
Section: Introductionmentioning
confidence: 99%
“…12 These motifs are characterized by distinct primary sequences and secondary structures, unique cofactor and pH dependencies, and specific substrate requirements. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Our group has been interested in understanding the functional limits of DNA-catalyzed RNA cleavage reactions. An ongoing investigation by our group aims to derive diverse DNAzymes that can efficiently cleave an RNA molecule at any location, given that different motifs favor the cleavage of a unique set of dinucleotide junctions (dinucleotide junction refers to base identities flanking the scissile site).…”
Section: Introductionmentioning
confidence: 99%